2015
DOI: 10.1111/1471-0307.12189
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of ovine milk yoghurt with inulin addition

Abstract: The purpose of this study was to elaborate prebiotic yoghurt using ovine milk and different inulin concentrations (0, 2 and 6%). Samples were submitted to laboratory analysis and two sensory tests with 100 consumers. The results of apparent viscosity and firmness determined by instrumental analysis of each yoghurt and control differed significantly. Just-About-Right showed consistency as the main attribute that varied in treatments. According to penalty analysis, prebiotic yoghurt containing 6% inulin had mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 51 publications
(74 reference statements)
3
24
0
1
Order By: Relevance
“…This finding is in agreement with Balthazar et al (2015) who produced a sheep's milk yogurt with a pH of 04.41. These authors also found an acidity (lactic acid % w/v) of 00.94, similar to our results.…”
Section: Physico-chemical Analysis Of Yogurtssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with Balthazar et al (2015) who produced a sheep's milk yogurt with a pH of 04.41. These authors also found an acidity (lactic acid % w/v) of 00.94, similar to our results.…”
Section: Physico-chemical Analysis Of Yogurtssupporting
confidence: 92%
“…Ewe milk, for example, has been proposed as an alternative milk source to feed infants who are allergic to milk from other species (Balthazar et al, 2017). Compared to bovine and caprine milk, ovine milk is richer in fat, proteins, ash, calcium, iron, manganese, phosphorus, zinc, all essential amino acids, most vitamins, medium-chain fatty acids and monounsaturated fatty acids (MUFA) (Balthazar et al, 2015;Park, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Balthazar et al . () in sensorial sheep milk yoghurt investigation found that the consumers more likely accept the yoghurt with inulin owing of lower acidity. Oliveira et al .…”
Section: Inulin Sensorial Aspectsmentioning
confidence: 97%
“…As formulações, em embalagens plásticas com capacidade para 80 mL, foram comprimidas com probe cilíndrico de 36 mm de diâmetro (P 36R) e penetração de 10 mm a velocidades de pré-teste e de teste constantes de 1 mm/s, velocidade pós-teste de 10 mm/s e trigger de 1g (BALTHAZAR et al, 2015).…”
Section: Preparação Das Bebidas Kefirunclassified